Therapeutic aspects of traumatic illness - I. V. Nagornov; A. A. Bova; A. N. Yanul (Military Medicine, 2026)
The article presents modern ideas about traumatic illness – the concept and definitions, classification, the main mechanisms in the development of the disease, approaches to diagnosis and the basic principles of the organization of medical care at the stages of medical evacuation. Co ncepts such as «visceral pathology in the wounded and affected of wartime» and «visceral pathology of wartime» should be distinguished and distinguished. It is also necessary to understand and highlight the role of a general practitioner in the treatment of visceral pathology in the wounded and those affected by traumatic illness. New periods have now been identified, pathogenesis, methods and techniques in early diagnosis and stage-by- stage treatment of traumatic illness have been supplemented. D ue to the frequent cases of attacks using unmanned aerial vehicles and precision weapons on residential and industrial facilities in the Russian Federation, the number of injured and injured has increased. The ongoing tense situation near the state border of the Republic of Belarus with an increasing likelihood of such incidents on our territory requires good training of medical workers in the knowledge of visceral pathology in traumatic illness.